Update on pre-ECMO evaluation and treatment for term infants in respiratory failure. Issue 6 (December 2022) - Fletcher, Kathryn L.; Chapman, Rachel
Abstract: The epidemiology, diagnostic and management approach to severe hypoxemic respiratory failure in the term and near-term neonate has evolved over time, as has the need for extracorporeal membrane oxygenation (ECMO) support in this patient population. Many patients who historically would have required ECMO support now respond to less invasive therapies, with patients requiring ECMO generally representing a higher risk and more heterogenous group of underlying diagnoses. This review will highlight these changes over time and the current available evidence for the diagnosis and management of these infants, as well as the current indications and relative contraindications to ECMO support when oxygen delivery cannot meet demand with less invasive management.